2021
DOI: 10.3390/brainsci11091185
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Learning in a Virtual Environment: The Role of Self-Efficacy Feedback and Individual Visuospatial Factors

Abstract: We examined the roles self-efficacy plays in environmental learning in terms of self-efficacy feedback and task-specific (navigation-based) self-efficacy. We manipulated self-efficacy using positive and neutral feedback to investigate the relationship between receiving positive feedback and environmental learning performance and subsequent recall. A total of 231 participants were administered visuospatial tasks, where 117 received positive feedback, and 114 received neutral feedback. Then, we tested environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…Looking at the beta values of our SEM model, each factor seems to contribute to environmental knowledge to a similar extent. This result differs from previous lab findings on learning from navigation in a desktop VE, when visuospatial abilities had a greater role than wayfinding inclinations (Hegarty et al, 2006 ; Meneghetti et al, 2021 ; Miola et al, 2021a , 2021b ; Pazzaglia et al, 2018 ). In the present study, the VE was navigated passively from an online video, and it showed a similar involvement of visuospatial abilities and wayfinding inclinations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Looking at the beta values of our SEM model, each factor seems to contribute to environmental knowledge to a similar extent. This result differs from previous lab findings on learning from navigation in a desktop VE, when visuospatial abilities had a greater role than wayfinding inclinations (Hegarty et al, 2006 ; Meneghetti et al, 2021 ; Miola et al, 2021a , 2021b ; Pazzaglia et al, 2018 ). In the present study, the VE was navigated passively from an online video, and it showed a similar involvement of visuospatial abilities and wayfinding inclinations.…”
Section: Discussioncontrasting
confidence: 99%
“…This means that women with higher abilities and inclinations can benefit from them similarly to men. While women with lower visuospatial abilities and inclinations may have lower environmental knowledge than men (in line with models inserting gender as an initial predictor, Miola et al, 2021a , 2021b ; Pazzaglia et al, 2018 ; see Additional file 1 ), the finding that gender does not affect the entity of the relationship between visuospatial factors and environmental knowledge highlights the importance of promoting and enhancing these human factors in environment knowledge acquisition, regardless of gender.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It includes eight contributions covering the application of VR for both children and adults. Six studies investigate which factors affect spatial navigation in VR: two investigate these factors during developmental ages (i.e., [10,11]), and the other four focus on young adults (i.e., [12][13][14][15]). One study reviews the applications of radial arm maze in both virtual and real versions (i.e., [16]), and the study by Zucchelli et al [17] shows how VR can be a proper differential diagnosis tool for mild agoraphobia disorders.…”
mentioning
confidence: 99%